Shinrin-yoku and its role in hypertension therapy - Rybak, Natalia; Czarnota, Jakub; Dobrzyński, Michał; Skubel, Tomasz (Journal of Education, Health and Sport, 2022)
Objective: This study aimed to evaluate the potential role of Shinrin-yoku (forest bathing) in the therapy of hypertension. Methods and materials: A literature search was conducted in the PubMed MEADLINE database of medical publications using the following keywords: Shinrin-yoku, forest bathing, hypertension, phytoncides Results: Hypertension is a serious problem in the Polish population. The data from the National Health Fund show that in 2020 almost 10 million adult Poles were affected by this disease, and over 14% of the entire pharmacy reimbursement budget was used to reimburse drugs for hypertension. Primary arterial hypertension is caused by a mixture of environmental and genetic factors, including obesity, mental stress, low physical activity, and excessive sodium intake. Although hypertension is usually asymptomatic, it contributes to serious complications such as left ventricular hypertrophy, impaired renal function, changes in the vessels of the retina, and finally to stroke or aortic dissection. The Shinrin-yoku (forest bathing) is becoming a worldwide recognized method used in preventative medicine and can play a substantial role in decreasing the number of patients suffering from hypertension. Conclusion: Shinrin-yoku (forest bathing) lowers blood pressure, heart rate, and the level of stress hormones, and therefore can be a prophylactic element in preventing the development of hypertension or an element of non-pharmacological therapy for this disease entity. Additionally, it has a positive effect on the immune system.